Elemental and isotopic composition of nitrogen, oxygen, and argon in Allan Hills ice cores - Bender, Michael; Higgins, John; Yan, Yuzhen (U.S. Antarctic Program (USAP) Data Center, 2021)
This file includes the d15N, O2/N2 ratio, Ar/N2 ratio, and d18O of O2 (d18Oatm) in Allan Hills ice cores (ALHIC1502 and ALHIC1503). This dataset replaces an earlier version of the elemental and isotopic composition in Allan Hills ice cores (DOI: 10.15784/601204) by adding new data from 60 depths in ALHIC1502 core (26.26 m to 175.74 m).